1984
DOI: 10.1002/1097-0142(19840501)53:9<1908::aid-cncr2820530917>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the breast with pseudosarcomatous metaplasia

Abstract: Twenty‐six cases of breast carcinoma demonstrating pseudosarcomatous metaplasia are described, and their clinical and pathologic aspects are correlated. The metaplastic elements include mature and immature bone, cartilage, myxoid stroma, loose fibromyxoid and dense spindle‐cell stroma, and anaplastic stroma with giant cell features. Light and electron microscopic examination demonstrated an orderly sequence of transformation and dedifferentiation of epithelial cells to become undifferentiated mesenchymal cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
107
2
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(116 citation statements)
references
References 38 publications
6
107
2
1
Order By: Relevance
“…Although the median age of MpBC patients was over 50 years of age in the literature (Kaufman et al, 1984;Oberman et al,1987;Rayson et al, 1999), the median age of our series was found to be about 5 years younger (45.5 years). Female preponderance is obvious but rarely male MpBC patients were reported in case series (Kuo et al, 2000).…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Although the median age of MpBC patients was over 50 years of age in the literature (Kaufman et al, 1984;Oberman et al,1987;Rayson et al, 1999), the median age of our series was found to be about 5 years younger (45.5 years). Female preponderance is obvious but rarely male MpBC patients were reported in case series (Kuo et al, 2000).…”
Section: Discussioncontrasting
confidence: 60%
“…MpBC has a lesser tendency to involve axillary lymph nodes compared to adenocarcinoma and reported to be in the range of 0-53% in some series (Gersell et al, 1981;Bauer et al, 1984;Kaufman et al, 1984;Chao et al, 1999;Rayson et al, 1999;Al Sayed et al, 2006;Bae et al, 2011). Although lower incidence of axillary lymph node involvement, classical surgery techniques such as radical mastectomy and modified radical mastectomy including axillary dissection were the preferred surgery choices in the literature (Pitts et al, 1991;Gutman et al, 1995;Rayson et al, 1999) except for one study (Caceres et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Metaplastic carcinoma of the breast is rare and it has been classified into two groups: squamous metaplasia (3.7% of all breast cancers) (1) and heterologous metaplasia (0.2%) (2). The exact histogenesis whether they are from a single progenitor cell or not is an issue to be solved.…”
mentioning
confidence: 99%
“…It has been reported that these tumors are more likely to occur in women over 50 years of age. 5,6 The patients usually describe a rapid growth with a short period of diagnosis. The tumors tend to have a circumscribed contour radiologically.…”
Section: Discussionmentioning
confidence: 99%